2019
DOI: 10.2147/jpr.s196129
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of transcutaneous electrical nerve stimulation on sleep in chronic low back pain: a real-world retrospective cohort study</p>

Abstract: Objective The purpose of this study was to determine if transcutaneous electrical nerve stimulation (TENS) improves sleep in chronic low back pain (CLBP). Background There is uncertainty over the effectiveness of TENS in CLBP. In most studies, pain intensity has been the primary outcome measure. Although sleep abnormalities are common in CLBP, sleep outcomes have not been evaluated in most studies of TENS effectiveness. Subjective and objective sleep measures are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Transcutaneous electrical nerve stimulation (TENS) is a noninvasive neuromodulating therapy that has been found to be effective in treating various chronic pain syndromes . After placing electrodes at the skin surface, electrical signals are transmitted that activate inhibitory interneurons and decrease nociceptor firing, ultimately resulting in inhibited transmission of ascending pain signals .…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) is a noninvasive neuromodulating therapy that has been found to be effective in treating various chronic pain syndromes . After placing electrodes at the skin surface, electrical signals are transmitted that activate inhibitory interneurons and decrease nociceptor firing, ultimately resulting in inhibited transmission of ascending pain signals .…”
Section: Introductionmentioning
confidence: 99%
“…3,22,24,66,79,80 Finally, activation of brain areas comprising the pain matrix 76,77 could have profoundly widespread analgesic effects, as well as improve mood, sleep, and other functions. 25,26,81 Various neurotransmitters are involved in pain inhibition, including GABA, glycine, noradrenaline, serotonin, and opioids. 82 The most relevant to remote TENS analgesia are likely to be the opioids.…”
Section: Modulation Of Central Pain Processingmentioning
confidence: 99%
“…Gozani et al evaluated changes in self-reported and objective measures of sleep in 554 participants using conventional TENS located on the lower leg over 10 weeks. 26 All participants reported chronic low-back pain with a prior history of back injury. Average TENS use was 40 hours per week.…”
Section: Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations